Evaluation of different sources of protein for growing horses - Tosi, Hugo; Toledo, Luiz Roberto Aguiar de; Leão, José Felipe de Souza; Crocci, Adalberto José; Bombarda, Augusto de Figueiredo; Vieira, Joaquim Manso; Santos, Gilberto de Figueiredo (Pesquisa Agropecuaria Brasileira, 2014)
This work was carried out at Posto de Equideocultura de Colina, SP, Brazil. Twelve colts and twelve fillies with average age of ten months at the beginning of the experiment were maintained in pastures of Coast cross grass (Cynodon dactylon ( L) Pers.) and received Rhodes grass hay (Chloris gayana Kunth.) and concentrate at 1% of five weight basis. The experiment lasted 168 days. The concentrates were prepared with three different sources of protein and all of them were included in the basal treatment. The average daily gain was 0.55 kg, and the average increase of the height at withers and heartgirth were of 9.31 cm and 21.21 cm, respectively. The statistical analysis did not show differences due to treatments, sex, and to treatment x Sex interation. The horses did not reach the maximum development expected, and this fact was attributed to the level of supplementation used, which was considered low to attend the nutrient requirements of the horses, and to the low quality of the roughage offered. The results allowed to conclude that all protein sources tested were satisfactory for growing horses and that it is necessary to use a higher level of concentrate supplementation as well as roughages of better quality during the winter period.